Sport und Gesellschaft : Sport and Society. Zeitschrift für Sportsoziologie, Sportphilosophie, Sportökonomie, Sportgeschichte (De Gruyter Oldenbourg, 2004)
The journal Sport und Gesellschaft - Sport and Society was founded in the year 2004. It is the official journal of the Sport Sociology Section of the DVS (German Association of Sport Science) and is published three times per year. The Journal presents original articles in the fields of sports sociology, sports philosophy, sports economics, and sports history written in German and English.